Acridone alkaloids from Glycosmis chlorosperma as DYRK1A inhibitors - Beniddir, M.A.A.; Le Borgne, E.A.; Iorga, B.L.A.; LoaÃ«c, N.B.C.; Lozach, O.B.; Meijer, L.B.C.; Awang, K.D.; Litaudon, M.A. (American Chemical Society, 2014)
Two new acridone alkaloids, chlorospermines A and B (1 and 2), were isolated from the stem bark of Glycosmis chlorosperma, together with the known atalaphyllidine (3) and acrifoline (4), by means of bioguided isolation using an in vitro enzyme assay against DYRK1A. Acrifoline (4) and to a lesser extent chlorospermine B (2) and atalaphyllidine (3) showed significant inhibiting activity on DYRK1A with IC50's of 0.075, 5.7, and 2.2 Î¼M, respectively. Their selectivity profile was evaluated against a panel of various kinases, and molecular docking calculations provided structural details for the interaction between these compounds and DYRK1A. Â© 2014 The American Chemical Society and American Society of Pharmacognosy.